2013
DOI: 10.1176/appi.ajp.2012.12060840
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Expected Value and Prediction Error Signaling in Youths With Disruptive Behavior Disorders During a Passive Avoidance Task

Abstract: Objective Youths with disruptive behavior disorders, including conduct disorder and oppositional defiant disorder, show major impairments in reinforcement-based decision making. However, the neural basis of these difficulties remains poorly understood. This partly reflects previous failures to differentiate responses during decision making and feedback processing and to take advantage of computational model-based functional MRI (fMRI). Method Participants were 38 community youths ages 10–18 (20 had disruptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
176
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(195 citation statements)
references
References 35 publications
15
176
4
Order By: Relevance
“…Our finding, however, may equally well allude to intrinsically heightened threshold for activating the reward system (i.e., hyporesponsivity), which could actually diminish reward sensitivity in some cases. Reward system hyporesponsivity to certain rewarding stimuli has indeed been theorized in relation to psychopathic traits, and assumed to impair reward representation and stimulus‐reward learning [Cohn et al, 2014; Finger et al, 2011; White et al, 2013]. Overall, our finding thus seems suggestive of a putative mechanism for biased reward processing in people with interpersonal traits of psychopathy, which speculatively could fuel instrumental antisocial interactions to satisfy personal desires and needs.…”
Section: Discussionsupporting
confidence: 58%
“…Our finding, however, may equally well allude to intrinsically heightened threshold for activating the reward system (i.e., hyporesponsivity), which could actually diminish reward sensitivity in some cases. Reward system hyporesponsivity to certain rewarding stimuli has indeed been theorized in relation to psychopathic traits, and assumed to impair reward representation and stimulus‐reward learning [Cohn et al, 2014; Finger et al, 2011; White et al, 2013]. Overall, our finding thus seems suggestive of a putative mechanism for biased reward processing in people with interpersonal traits of psychopathy, which speculatively could fuel instrumental antisocial interactions to satisfy personal desires and needs.…”
Section: Discussionsupporting
confidence: 58%
“…This shows that psychopathic traits are associated with abnormal processing of reinforcement information. White et al (2013) found abnormal ventromedial prefrontal cortex functioning in CD children during a decision making task, but found no differences between subjects with high or low CU traits. Finger et al (2011) compared teenage subjects with DBD disorders (mean age=14.1 years) to healthy controls (mean age=13.1 years) and found hypoactivity in the orbitofrontal cortex in response to early stimulus-reinforcement exposure and rewards.…”
Section: Prefrontal Cortexmentioning
confidence: 77%
“…Youth with CU traits, however, also appear to derive positive rewards from deviant behavior (e.g., social status from bullying [35]) and fail to encode outcomes that violate societal expectancies [36,37]. In addition, youth with CU traits show significant disruption in processing punishment information [38,39]. This evidence suggests that high CU youth are more likely to initiate early, escalate, and/or persist in deviant behaviors because they are less mindful of its negative consequences [40][41][42][43][44].…”
Section: Exemplar Phenotype: Callous-unemotional Traitsmentioning
confidence: 99%
“…T0 research has further shown that these deficits are neurally subserved by abnormalities in the "motivational network" (mesocorticolimbic dopamine pathways) that mediates reward-based decision-making [30,45]. Neuroimaging studies have related the decision-making impairment in CU youth to reduced representation of expected value within the ventromedial prefrontal cortex (how much reward/ punishment is associated with a response choice) and prediction error signaling within caudate (signaling the difference between the reward expected and that received) [39]. These data suggest a neurobiological mechanism that may explain why CU youth would exhibit poorer and slower learning of reinforcements associated with objects and actions.…”
Section: Exemplar Phenotype: Callous-unemotional Traitsmentioning
confidence: 99%